Dairy facility design - Muprhy, J.P. (Kansas Agricultural Experiment Station, 2012)
When planning new construction or major modification of a dairy system, consider: • calf, heifer, dry cow, and milking cow housing; • feed types, handling equipment, and storage; • manure handling method; • milking system and equipment; • labor requirements; • building environment; • sanitary and pollution control regulations; • future expansion. Many dairy farmers produce their own feeds and raise their own herd replacements. The needs of each groups require different housing, feeding, storage, and handling systems.
The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy; Facility design; Housing; Feed